Compensation in Philosophical Review: Ontology, Epistemology, and Axiology - Sudrajat, Jajat; Loke Siow, Hong; Adi Permana, Ibar (International Journal of Social Science, Education, Communication and Economics, 2025)
Compensation is part of the resource management function which is related to various types of rewards that individuals receive as rewards for employees who have carried out their work duties. The total reward received by employees who have done their work is managed by the company by creating a policy which is also known as input-output exchange between the company and its employees. To optimally understand the nature of compensation, the types and forms of compensation and the benefits of compensation, it can be viewed from the science of philosophy. Compensation is discussed in detail using philosophy through the dimensions of ontology, epistemology, and axiology. So, with this aim, organizations or companies can get a complete picture of compensation and can make efforts to optimize compensation so that it can bring positive benefits and prevent negative things that can arise if it is not handled correctly. This research discusses compensation from a philosophical perspective in the dimensions of ontology, epistemology and axiology using a qualitative approach. The research results show that from the perspective of philosophical knowledge, compensation can be explained in three dimensions, namely: ontology, epistemology, and axiology. In the ontological dimension, compensation includes the true meaning of compensation which can be proven to exist in every organization. The epistemological dimension of compensation is related to the basic science, forms, characteristics, and types of all existing compensation. Finally, in the axiological dimension, the discussion of compensation includes the relationship between compensation and value, namely the feasibility of compensation to be developed, as well as the function and benefits of compensation in the organization. In the end, compensation needs to be managed so that it can provide more optimal benefits in the continuity of an organization's activities.